Molecular and clinical analyses of 84 patients with tuberous sclerosis complex - Hsieh Chia-Jung; Chen Pau-Chung; Chen Chih-Chuan; Liou Horng-Huei; Chien Shu-Chin; Su Yi-Ning; Hung Chia-Cheng; Chen Chih-Ping; Lee Wang-Tso; Lin Win-Li; Lee Chien-Nan (BMC, 2006)
Abstract Background Tuberous sclerosis complex (TSC) is an autosomal dominant disease characterized by the development of multiple hamartomas in many internal organs. Mutations in either one of 2 genes, TSC1 and TSC2, have been attributed to the development of TSC. More than two-thirds of TSC patients are sporadic cases, and a wide variety of mutations in the coding region of the TSC1 and TSC2 genes have been reported. Methods Mutational analysis of TSC1 and TSC2 genes was performed in 84 Taiwanese TSC families using denaturing high-performance liquid chromatography (DHPLC) and direct sequencing. Results Mutations were identified in a total of 64 (76 %) cases, including 9 TSC1 mutations (7 sporadic and 2 familial cases) and 55 TSC2 mutations (47 sporadic and 8 familial cases). Thirty-one of the 64 mutations found have not been described previously. The phenotype association is consistent with findings from other large studies, showing that disease resulting from mutations to TSC1 is less severe than disease due to TSC2 mutation. Conclusion This study provides a representative picture of the distribution of mutations of the TSC1 and TSC2 genes in clinically ascertained TSC cases in the Taiwanese population. Although nearly half of the mutations identified were novel, the kinds and distribution of mutation were not different in this population compared to that seen in larger European and American studies.